Chemical production of activated carbon from green coffee with adsorption isotherm support by Taguchi model - Bozaci, Gozde; Acarali, Nil (ELSEVIER, 2023)
In this study, the aim was to produce the activated carbon from green coffee for use in liquid phase applications with adding zinc borate which was a boron chemical. Phosporic acid was chosen as the chemical activation material and different reaction parameters (percent of phosporic acid, amount of zinc borate) were tested during the process of chemical activation. The experimental sets were determined by using Taguchi optimization method and optimal conditions were obtained. Taguchi optimization method was preferred to reach optimum process parameters by using time and material in the most beneficial way. The effects of the process parameters (microwave drying time, temperature of carbonization and duration of carbonization) were investigated to determine the optimal sample. The characteristic properties of the obtained activated carbons were determined with Fourier transform infrared spectroscopy (FT-IR), Brunauer-Emmett-Teller surface area analysis (BET), Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis. The samples of activated carbon produced were used for determination of the iodine number and the adsorption of heavy metal Cr (VI) ions from solution. Analysis and studies of adsorption showed that activated carbon was produced successfully. The activated carbon was evaluated in liquids phase applications and Langmuir isotherm was found more applicable and experimental data was proper with the second-order kinetic model.
Keywords: Activated carbon; Green coffee; Taguchi; Adsorption; Boron; REMOVAL; SHELLS; DYE; CO2; Chemistry